Celebration Time: 20 Years of Brazilian Administration Review - Tomás de Aquino Guimarães; Rogério Hermida Quintella; Jorge Manoel Teixeira Carneiro; Salomão Alencar de Farias; Carlo Gabriel Porto Bellini; Ivan Lapuente Garrido; Ricardo Limongi (BAR: Brazilian Administration Review)
The Brazilian Administration Review (BAR) has established itself as a cornerstone of academic excellence in business and public administration in Brazil and internationally. Over its two decades, the journal has evolved from an ambitious initiative to address the specific needs of the Brazilian academic community to a globally recognized platform for high-quality scholarly work. Since its inception, with two issues per year, BAR has shown remarkable growth in publication frequency and its reach and impact. This growth is reflected in our submission numbers, which have increased substantially each yearly. In. In this sense, this editorial reflects on the motivations behind BAR’s creation, the challenges it has overcome, and its aspirations for the future, weaving insights from the experiences of its editors and the broader academic community...